2009
DOI: 10.1016/j.cell.2009.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Protein Architecture of the Human Kinetochore Microtubule Attachment Site

Abstract: Centromeric chromatin – spindle microtubule interactions mediated by kinetochores drive chromosome segregation. We have developed a two-color fluorescence light microscopy method that measures average label separation, Delta, at < 5 nm accuracy — to elucidate the protein architecture of human metaphase kinetochores. Delta analysis, when correlated with tension states of spindle-attached sister kinetochore pairs, provided information on mechanical properties of protein linkages within kinetochores. Treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

44
491
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 324 publications
(539 citation statements)
references
References 59 publications
44
491
1
3
Order By: Relevance
“…Our data could be explained by a modification of the "amphipathic" superhelix model if helical segments were oriented radially with their long axes perpendicular to the chromosome axis. Such an orientation would expose some CENP-A and H3 on the outer surface of the chromosome, but is difficult to reconcile with immunoelectron microscopy and super-resolution colocalization of other kinetochore proteins with CENP-A by fluorescence microscopy, all of which indicate that CENP-A seems to provide a basal layer to the kinetochore that does not penetrate significantly into the chromosome interior (13,46,47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data could be explained by a modification of the "amphipathic" superhelix model if helical segments were oriented radially with their long axes perpendicular to the chromosome axis. Such an orientation would expose some CENP-A and H3 on the outer surface of the chromosome, but is difficult to reconcile with immunoelectron microscopy and super-resolution colocalization of other kinetochore proteins with CENP-A by fluorescence microscopy, all of which indicate that CENP-A seems to provide a basal layer to the kinetochore that does not penetrate significantly into the chromosome interior (13,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…In both models, CENP-A and H3 nucleosomes face the external surface, enabling the binding of all CCAN proteins. CENP-C could bind to the more internal CENP-A blocks, crosslinking several layers and explaining the similar oscillations undergone by CENP-A and CENP-C when kinetochores are under tension exerted by microtubules (47). The KMN network assembles in mitosis on top of the CCAN and binds microtubules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the above mentioned reports indicated a key role of DYNLT1 in modulating mPT and MT network stability, we hypothesized that phosphorylation of DYNLT1, especially on S82, might occur in hypoxia, based on our previous work in which we showed that hypoxia-activated p38/MAPK signaling pathway initiates MT disruption and alters cell viability by phosphorylating the downstream effector (Hu et al, 2010). In order to generalize these observations, we chose H9c2 and HeLa cells (Brito and Rieder, 2009;Wan et al, 2009) to study hypoxiareduced MTs disruption and mitochondrial permeabilization related to S82. We used site-directed mutagenesis of the phosphorylation site to obtain phosphomimic and dephosphomimic mutants.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous immuno-electron microscopy (16)(17)(18) and superresolution microscopy (19)(20)(21) studies have mapped the locations of CCAN components relative to one another, the packing of the chromatin fiber in centrochromatin remains unknown. Early studies of stretched chromosomes suggested a repeating "subunit" structure for the kinetochore (1,22).…”
mentioning
confidence: 99%